Analisis Pengaruh PER, MVA, dan EVA terhadap Harga Saham dengan Tahun COVID-19 sebagai Variabel Moderasi Pada Perusahaan Sektor Kesehatan yang Terdaftar di BEI Periode 2018-2021: (Studi Kasus Perusahaan Sektor Kesehatan Periode 2018-2022) - Rian Martin Silitonga; Jack Febriand Adel; Ardiansyah Ardiansyah (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2023)
The purpose of this study was to determine the effect of PER, MVA, and EVA on stock prices with COVID-19 Year as a moderating variable in health sector companies listed on the IDX for the 2018-2022 period. The sample used was 40 data. The analysis method used is multiple linear regression analysis and Moderated Regression Analysis (MRA). Based on the results of the analysis, it was found that Price Earning Ratio (PER), Market Value Added (MVA), and COVID-19 Year have a positive and significant effect on stock prices, but the Economic Value Added (EVA) variable has a negative and significant effect on stock prices. The COVID-19 year can weaken the relationship between PER and EVA on stock prices, but the COVID-19 year can strengthen the relationship between MVA on stock prices.